Spletna slovenščina pri Slovencih v Nemčiji: jezikovne značilnosti objav na Facebooku - Štumberger, Saška (Slavia Centralis, 2020)
Internet Slovenian used by Slovenians living in Germany: linguistic features of Facebook postsThe article presents the internet Slovenian used by Slovenians living in Germany by means of analysis of Facebook posts in the group Slovenci v Nemčiji. The group members belong to the young generation and have recently moved to Germany. They often exchange information on administrative procedures. Due to these circumstances of their communication, the prevailing language variety expected is standard and colloquial language and a high share of technical terms from the field of administration.
Keywords: Slovenians in Germany; emigration; social networks; language varieties; technical terms; standard language